Fluorescent whitening agent containing naphthyl and preparation method thereof
By designing and synthesizing a fluorescent whitening agent containing naphthyl group, 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene, the poor whitening effect of traditional fluorescent whitening agents is solved. and the problem of poor sun fastness, it achieves efficient fluorescence emission and stability, and is suitable for the textile and paper industry.
Patent Information
- Application Number
- CN202411356793.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional fluorescent whitening agents have poor whitening effect and poor sun fastness during use, making it difficult to meet the needs of high-efficiency and good color fastness in textiles, papermaking and other industries.
A fluorescent whitening agent containing naphthyl group was designed, 3-naphthyl-4-methyl-2,5-bis(benzothiazole-2-yl)thiophene, which uses a thiophene ring through molecular structure optimization and synthesis new routes. , the combination of benzothiazole group and naphthyl group optimizes the photophysical properties of the compounds, and the target compounds are synthesized by methods such as density functional theory and Suzuki-Miyaura coupling reaction.
It has achieved strong absorption and efficient fluorescence emission in the ultraviolet light region, with excellent fluorescence quantum yield, thermal stability, light stability and whitening effect, significantly improving the whiteness and brightness of textiles and paper materials, and Maintain good performance during washing.
Smart Images

Figure CN119264129A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluorescent whitening agents, and in particular to a naphthyl-containing fluorescent whitening agent and a preparation method thereof. Background Art
[0002] Fluorescent whitening agents are a class of organic compounds that can absorb ultraviolet light and emit visible light. They can be used to improve the whiteness and brightness of materials such as textiles, paper, and plastics. According to the chemical structure, fluorescent whitening agents can be divided into several types, such as benzothiazole, imidazole, pyridine, and thiophene. Among them, compounds with thiophene ring as the parent core and containing benzothiazole groups have attracted much attention due to their excellent optical properties and application effects.
[0003] Fluorescent whitening agents have been widely used in textile, paper, plastic and other industries. In the textile field, the use of fluorescent whitening agents can significantly improve the whiteness of fiber fabrics, improve their visual effects, and increase product added value. In the papermaking industry, fluorescent whitening agents can compensate for the yellow cast of paper, increase paper brightness, and improve printability. For plastic products, adding fluorescent whitening agents can mask the yellow hue of the plastic itself and obtain an ideal white effect.
[0004] Traditional fluorescent whitening agents have some problems in use, such as poor whitening effect and poor light fastness. Therefore, the development of new and efficient fluorescent whitening agents is of great significance for the sustainable development of industries such as textiles and papermaking. In recent years, researchers have been committed to designing and synthesizing thiophene-based fluorescent whitening agents with novel structures and excellent performance, in order to obtain new fluorescent whitening materials with high whitening efficiency and good color fastness.
[0005] The present invention is suitable for a naphthyl-containing fluorescent whitening agent: 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene.
[0006] Based on previous research, this invention intends to optimize the molecular structure of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene fluorescent whitening agent through molecular structure design and theoretical calculation, and explore a new efficient synthesis route. By testing and analyzing the photophysical properties and application performance of the target compound, its application potential as a new type of efficient fluorescent whitening agent is evaluated. Summary of the invention
[0007] The structure design of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene based on molecular orbital theory:
[0008] The thiophene ring is an important building block of organic optoelectronic functional materials, and has good charge transfer performance and optical properties. Therefore, the present invention selects the thiophene ring as the central mother nucleus of the fluorescent whitening agent molecule. The introduction of benzothiazole groups at the 2, 5-positions of the thiophene ring can construct a large conjugated system, expand the degree of π electron delocalization of the molecule, and help improve the photophysical properties of the compound. At the same time, the introduction of a naphthyl group at the 3-position of the thiophene ring can not only increase the degree of conjugation of the molecule, but also play a role in inhibiting H-aggregation. In addition, the introduction of a methyl group at the 4-position of the thiophene ring can increase the HOMO energy level of the molecule, reduce the HOMO-LUMO band gap, and further optimize the optical properties of the compound. Based on the above analysis, the present invention designs the molecular structure of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene, such as Figure 1 As shown, its structure diagram is .
[0009] In order to obtain a stable conformation of the 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene molecule, the present invention uses the B3LYP functional of density functional theory (DFT) to optimize the molecular structure with the 6-31G (d) basis set, and calculates the total energy of the molecule. The results show that the optimized molecule is in a planar conformation, and the planes of the naphthalene ring and the thiophene ring are basically coplanar, which is conducive to intramolecular charge transfer. In addition, the total energy of the molecule is -2976.59 au, and the structure is relatively stable.
[0010] The frontier orbitals of molecules, namely the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO), have an important influence on the photophysical properties of the compound. Generally speaking, the HOMO electron cloud distribution reflects the molecule's ability to donate electrons, the LUMO electron cloud distribution reflects the molecule's ability to accept electrons, and the energy gap between HOMO and LUMO determines the excitation and emission wavelengths of the molecule. The HOMO-LUMO energy gap of a molecule is a key parameter for evaluating its optical properties. The smaller the energy gap, the longer the wavelength of the molecule's absorption and emission. According to the calculation results of B3LYP / 6-31G (d), the HOMO and LUMO orbital energy levels of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene are and , thus obtaining the HOMO-LUMO energy gap of the molecule:
[0011] ;
[0012] This energy gap value is located at the ultraviolet end of visible light, indicating that the target molecule has strong absorption in the ultraviolet region. At the same time, according to the Planck-Einstein relationship:
[0013] ;
[0014] in, is the Planck constant ( ), is the light frequency, is the speed of light ( ), As the corresponding wavelength, the maximum absorption wavelength of the molecule can be estimated:
[0015] ;
[0016] The above theoretical calculations show that the maximum absorption wavelength of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene molecules is about 374nm, which is in the ultraviolet spectrum region and is consistent with the application requirements of fluorescent whitening agents.
[0017] The theoretical calculation results of the frontier orbital energy levels and energy gaps of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene are listed in Table 1.
[0018] Table 1 Calculated values of frontier orbital energy levels and energy gaps of target molecules:
[0019] ;
[0020] As can be seen from Table 1, the target molecule has a moderate HOMO-LUMO energy gap, which is conducive to strong absorption and efficient fluorescence emission in the ultraviolet-visible light region, and has a molecular structural basis for becoming an excellent fluorescent whitening agent.
[0021] The UV-Vis absorption spectrum of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene molecule was simulated at the 6-31+G(d) basis set level using the CAM-B3LYP functional of time-dependent density functional theory (TD-DFT), and the vertical transition energy, oscillator strength and main orbital contribution of the first 20 singlet excited states were calculated. Table 2 shows the theoretical absorption spectrum of the molecule in vacuum and N,N-dimethylformamide (DMF) solvent. The target molecule has obvious characteristic absorption peaks in the ultraviolet region, among which the strongest absorption peaks are located at 367nm (vacuum) and 388nm (DMF), corresponding to HOMO →LUMO transitions, and the oscillator strengths are 0.671 and 1.053, respectively, indicating that the molecule has a high light absorption ability.
[0022] Table 2 Partial electronic transitions and contributing orbitals of target molecules:
[0023] ;
[0024] In Table 2, represents the excitation energy, is the corresponding wavelength, Theoretical calculation results show that the solvent effect causes the absorption peak of the molecule to have a significant red shift. The maximum absorption peak in DMF is 21nm red-shifted compared with vacuum, and the absorption intensity is also greatly enhanced, indicating that polar solvents are beneficial to improve the light absorption performance of molecules.
[0025] At the TD-DFT / CAM-B3LYP / 6-31+G(d) theoretical level, the geometric configuration of the first excited singlet state (S1) of the molecule was optimized and the fluorescence emission spectrum of the molecule was calculated based on this. The results show that the maximum fluorescence emission wavelength of the target molecule in DMF solvent is 432nm, the Stokes shift is 44nm, and the oscillator intensity of the emission peak is 1.227, indicating that it has a high fluorescence quantum yield.
[0026] Fluorescence quantum yield ( ) is an important parameter for evaluating the luminous efficiency of fluorescent materials, which indicates the proportion of energy released in the form of fluorescence after the molecule absorbs photons. According to the Strickler-Berg formula, the molecular The transition dipole moments of its absorption and emission peaks can be ) and oscillator strength ( ) Estimate:
[0027] ;
[0028] The subscripts abs and em represent the physical quantities corresponding to the absorption and emission peaks, respectively. is the light frequency. Using the data in Table 2, the theoretical fluorescence quantum yield of the molecule is calculated by the following steps:
[0029] (1) The transition dipole moment corresponding to the absorption peak is:
[0030] ;
[0031] in, is the oscillator strength of the S1 excited state in DMF, taken from Table 2.
[0032] (2) Similarly, calculate the transition dipole moment corresponding to the emission peak:
[0033] ;
[0034] in, is the oscillator strength of the emission peak.
[0035] (3) Substituting the above results into the Strickler-Berg formula, we can obtain the theoretical fluorescence quantum yield of the molecule:
[0036] ;
[0037] It can be seen that the fluorescence quantum yield of the 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene molecule obtained by theoretical calculation is as high as 0.987, indicating that it has excellent fluorescence emission efficiency and has great potential to be developed into a high-performance fluorescent whitening agent.
[0038] Design of synthetic route of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene fluorescent brightener:
[0039] The preparation of fluorescent whitening agent molecules requires solving two key problems: one is the construction of a heterologous tricyclic (thiophene-benzothiazole) system; the other is the introduction of substituents such as naphthyl and methyl. Based on this, this paper conducted a retrosynthetic analysis of the synthesis of the target compound and split it into the following two modules: 2,5-dibromothiophene was prepared by boric acid esterification to prepare 2,5-dibromo-4-boronic acid pinacol ester thiophene; 3-bromomethylnaphthalene and 2-bromobenzothiazole. The intermediates of the two modules were then constructed into a tricyclic skeleton through steps such as Suzuki-Miyaura coupling, and naphthyl and methyl were introduced to obtain the final target product.
[0040] Design of synthetic route of 2,5-dibromo-4-boronic acid pinacol ester thiophene intermediate:
[0041] 2,5-Dibromothiophene and pinacol undergo borate esterification reaction under the catalysis of tetrakis(triphenylphosphine)palladium to generate 2,5-dibromo-4-boric acid pinacol ester thiophene. The reaction equation is as follows:
[0042] ;
[0043] The raw materials of this route are easily available, the reaction conditions are mild, and the product is easy to separate and purify. It is an effective method for preparing 2,5-dibromo-4-boronic acid pinacol ester thiophene.
[0044] 3-Bromomethylnaphthalene is a commercial reagent and can be purchased and used directly without additional synthesis.
[0045] Optimization of the synthetic route of the target product 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene:
[0046] After obtaining the two key intermediates 2,5-dibromo-4-boronic acid pinacol ester thiophene and 3-bromomethylnaphthalene, this paper designed and optimized the synthesis route of the target compound by referring to the literature and combining the research foundation of this research group: palladium-catalyzed Suzuki-Miyaura coupling method.
[0047] Palladium-catalyzed Suzuki-Miyaura coupling route:
[0048] 2,5-Dibromo-4-boronic acid pinacol ester thiophene and 3-bromomethylnaphthalene undergo Suzuki-Miyaura coupling reaction under the catalysis of tetrakis(triphenylphosphine)palladium to generate 2,5-dibromo-3-naphthylthiophene. 2,5-Dibromo-3-naphthylthiophene undergoes bromination reaction under the action of N-bromosuccinimide (NBS) to obtain 2,5-dibromo-4-bromomethyl-3-naphthylthiophene. 2-Bromobenzothiazole and pinacol undergo boric acid esterification reaction under the catalysis of tetrakis(triphenylphosphine)palladium to generate 2-benzothiazole-4-boronic acid pinacol ester. 2,5-Dibromo-4-bromomethyl-3-naphthylthiophene and 2-benzothiazole-4-boronic acid pinacol ester underwent Suzuki-Miyaura coupling reaction catalyzed by tetrakis(triphenylphosphine)palladium to obtain the target product 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene.
[0049] The key reaction equation is as follows:
[0050] ;
[0051] ;
[0052] ;
[0053] Advantages: high total yield, relatively mild reaction conditions, simple post-processing. Disadvantages: many reaction steps, and the palladium catalyst is relatively expensive.
[0054] This synthetic route uses the Suzuki-Miyaura coupling reaction as a key step and has the following advantages:
[0055] (1) Mild reaction conditions and good functional group compatibility;
[0056] (2) The by-products are mainly inorganic salts, which are easy to separate and purify;
[0057] (3) Boronate reagents are stable and easy to store and operate;
[0058] (4) The reaction has high regioselectivity and stereoselectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is the structural formula of the 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene fluorescent whitening agent proposed in the present invention.
[0060] Figure 2 This is the UV-Vis absorption spectrum of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene (DMF solution).
[0061] Figure 3This is the thermal stability analysis (TGA-DSC curve) of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene.
[0062] Figure 4 The photostability of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene.
[0063] Figure 5 The washing fastness of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene on polyamide 66 fabric. DETAILED DESCRIPTION
[0064] Reagents and instruments: 2,5-dibromothiophene (97%, Aladdin), pinacol (98%, Aladdin), tetrakis(triphenylphosphine)palladium (99%, Sigma-Aldrich), N-bromosuccinimide (NBS, 98%+, Aladdin), 3-bromomethylnaphthalene (98%, J&K), 2-aminobenzothiazole (98%, J&K), anhydrous (99%, Sinopharm) and other reagents were of analytical grade and used directly without further purification. Thin layer chromatography (TLC) silica gel plates (Qingdao Ocean Chemical Plant). Column chromatography silica gel (300-400 mesh, Qingdao Ocean Chemical Plant). NMR was measured using a Brucker AM 400 nuclear magnetic resonance spectrometer with TMS as the internal standard, and mass spectra were measured using a Waters Micromass GTC Premier mass spectrometer.
[0065] Synthesis steps of 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene:
[0066] Step 1: Preparation of 2,5-dibromo-4-boronic acid pinacol ester thiophene. Dissolve 1.5726 g (6.50 mmol) 2,5-dibromothiophene, 1.6658 g (13.00 mmol) pinacol, and 0.1849 g (0.16 mmol) tetrakis(triphenylphosphine)palladium in 50 mL toluene and heat under reflux for 12 h. Evaporate the solvent under reduced pressure, and separate the residue by silica gel column chromatography using petroleum ether / ethyl acetate (20:1) as the eluent to obtain 1.69 g of a white solid with a yield of 80.4%.
[0067] Step 2: Preparation of 2,5-dibromo-3-naphthylthiophene. Add 1.6201 g (5.00 mmol) of 2,5-dibromo-4-boronic acid pinacol ester thiophene, 1.2456 g (5.00 mmol) of 3-bromomethylnaphthalene, 2.0732 g (15.00 mmol) of anhydrous potassium carbonate, and 0.2311 g (0.20 mmol) of tetrakis(triphenylphosphine)palladium to a 50 mL round-bottom flask, replace N2 three times, inject 20 mL of degassed 1,4-dioxane and 10 mL of deionized water, and stir at 90 °C for 10 h. After the reaction is completed, pour the reaction solution into 50 mL of water, extract with dichloromethane (30 mL × 3), combine the organic phases and dry with anhydrous sodium sulfate. The mixture was filtered and the solvent was removed by distillation under reduced pressure. The crude product was separated by silica gel column chromatography [eluent: V (petroleum ether): V (ethyl acetate) = 30: 1] to obtain 1.45 g of a light yellow solid with a yield of 72.3%.
[0068] Step 3: Bromination reaction of 2,5-dibromo-3-naphthylthiophene. Weigh 1.6051 g (4.00 mmol) 2,5-dibromo-3-naphthylthiophene and 0.7120 g (4.00 mmol) NBS in a 50 mL round-bottom flask, add 25 mL carbon tetrachloride, and heat under reflux for 4 h in the dark. After cooling to room temperature, filter, wash the filter cake with a small amount of carbon tetrachloride, and dry to obtain 1.51 g of white solid powder, with a yield of 78.6%.
[0069] Step 4: Preparation of 2-bromobenzothiazole-4-boronic acid pinacol ester. Add 2.1207 g (10.00 mmol) 2-bromobenzothiazole, 2.5626 g (20.00 mmol) pinacol, 3.4553 g (25.00 mmol) anhydrous potassium carbonate, 0.5778 g (0.50 mmol) tetrakis(triphenylphosphine)palladium into a 100 mL three-necked flask, replace N2 three times, inject 50 mL degassed 1,4-dioxane, and stir at 90 °C for 12 h. The reaction solution was cooled to room temperature, filtered, the filter cake was washed with ethyl acetate, the filtrate was combined, and the solvent was evaporated under reduced pressure to obtain a crude product. The crude product was separated and purified by silica gel column chromatography [eluent: V (petroleum ether): V (ethyl acetate) = 5: 1] to obtain 2.13 g of a white solid with a yield of 84.8%.
[0070] Step 5: Suzuki-Miyaura coupling reaction. Add 1.4406 g (3.00 mmol) 2,5-dibromo-4-bromomethyl-3-naphthylthiophene, 2.2602 g (9.00 mmol) 2-benzothiazole-4-boronic acid pinacol ester, 2.4873 g (18.00 mmol) anhydrous potassium carbonate, 0.3467 g (0.30 mmol) tetrakis(triphenylphosphine)palladium into a 100 mL three-necked flask, replace N2 three times, inject 60 mL degassed 1,4-dioxane and 30 mL deionized water, and stir at 90 °C for 12 h. After the reaction, pour the reaction solution into 150 mL water and extract with ethyl acetate (50 mL × 3). The organic phases were combined, dried over anhydrous magnesium sulfate, filtered, and desolventized. The residue was separated by silica gel column chromatography [eluent: V (petroleum ether): V (dichloromethane) = 1:1] to obtain 1.34 g of a yellow solid with a yield of 84.0%.
[0071] The characterization results are as follows:
[0072] NMR (400MHz, ) (ppm): 8.42 (s, 1H), 8.32 (d, =8.0Hz, 1H), 8.12(d, =8.8Hz, 2H), 8.05(d, =7.6 Hz, 2H), 7.92 (d, =8.4Hz, 2H), 7.86(d, =8.0Hz, 1H), 7.56-7.49 (m, 4H), 7.39 (t, =7.6Hz, 2H), 2.31 (s, 3H).
[0073] NMR (100MHz, ) (ppm): 166.8, 155.1, 152.9, 139.6, 137.1, 133.9, 133.4, 133.2, 131.8, 130.7, 12 9.8, 129.0, 127.7, 127.0, 126.3, 125.6, 125.2, 124.5, 123.6, 121.8, 121.5, 16.1.
[0074] HRMS (ESI) : Calcd for 531.0772; Found 531.0769.
[0075] After obtaining the target product, a series of tests were performed on the target product.
[0076] UV-Vis absorption spectrum:
[0077] The target compound was prepared to a concentration of mol / L DMF solution, with DMF as reference, was measured on a Shimadzu UV-2700 UV-visible spectrophotometer with a scanning range of 300-500nm. The results are as follows: Figure 2 As shown, The maximum absorption wavelength of the target compound was measured to be 388 nm, and the molar absorption coefficient was , indicating that it has strong absorption capacity in the ultraviolet region. The experimental value is highly consistent with the theoretical calculation result (388nm), which confirms the rationality of the previous molecular design.
[0078] Fluorescence emission spectrum:
[0079] The preparation concentration is mol / L of the target compound in DMF dilute solution, scan the emission spectrum on a 970CRT fluorescence spectrophotometer with 388nm as the excitation wavelength. ; The result is as follows Figure 2 As shown, the maximum emission peak of the compound is located at 432nm, and the Stokes shift is 44nm compared with its absorption peak. Using quinine sulfate as a reference, its fluorescence quantum yield is measured to be as high as 0.91, close to the theoretical prediction value (0.987), indicating that the compound has excellent fluorescence emission efficiency.
[0080] The theoretically calculated photophysical properties of the target compound were compared with the experimental test values, and the results are listed in Table 4. It can be seen that the experimental values are in good agreement with the theoretically predicted values, and the relative errors are all within 5%, indicating that the theoretical calculation method used in the early stage is reliable and can provide strong guidance for the design of such fluorescent whitening agent molecules.
[0081] Table 4 Comparison of theoretical calculated values and experimental values of photophysical properties of target compounds:
[0082] ;
[0083] Thermal stability and light stability test:
[0084] like Figure 3As shown, the thermal stability of the target compound was tested by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). TGA results showed that the compound had an initial thermal decomposition temperature of up to 389°C and had good thermal stability within the operating temperature range of fluorescent whitening agents. The results showed that the melting point of the target compound was 298°C, which was higher than most commercial fluorescent whitening agents, which was conducive to its stability under high temperature conditions.
[0085] The photostability test was conducted in a BL-GHX-V type light test chamber, using a xenon lamp as the light source, with a power of 500W and a 290nm filter to filter out short-wave ultraviolet rays. The target compound was loaded on polyamide 66 fabric, placed on a sample rack, and compared with a standard blue wool cloth, and continuously illuminated for 35 hours. The fabric was tested under a D65 light source before and after illumination. The whiteness under the field of view is as follows Figure 4 As shown in the figure, the whiteness of the fabric decreased by less than 2% after 35 hours of illumination, indicating that the target compound has excellent light stability.
[0086] Standard whitening power in polyamide 66 fabrics ( ):
[0087] Prepare an aqueous solution with a target compound concentration of 0.2% (owf), dip polyamide 66 fabric into it, and bake at 100°C for 3 minutes. Test fabric under D65 light source The whiteness under the visual field is compared with the untreated original white fabric, and the standard whitening power is calculated according to the following formula:
[0088] ;
[0089] in, and The whiteness of the fabric after fluorescent whitening and the original white fabric, respectively. The standard whitening power of the target compound on polyamide 66 fabric was measured to be 25.3, which is higher than the commercial fluorescent whitening agent FWA-6 (23.0), indicating that the compound has an excellent whitening effect.
[0090] Whitening power retention after 20 standard washing cycles ( ):
[0091] The fluorescently whitened polyamide 66 fabric was washed in a standard washing machine for 20 cycles according to the 2A washing condition in AATCC standard 61-2006. Samples were taken every 5 washes to test the whiteness of the fabric and compared with the whiteness of the sample after whitening without washing ( ) and calculate the whitening power retention rate after washing according to the following formula:
[0092] ;
[0093] in, is the whiteness value of the fabric after washing 20 times. Figure 5 The results showed that the whitening power retention rate of the target compound on polyamide 66 fabric was still as high as 92% after washing 20 times, which was better than FWA-6 (82%), indicating that it had excellent washing fastness.
[0094] The target compound 3-naphthyl-4-methyl-2,5-bis(benzothiazol-2-yl)thiophene was characterized by nuclear magnetic resonance, mass spectrometry and other methods. The test results of UV-visible absorption spectrum and fluorescence emission spectrum showed that the compound had strong absorption in the ultraviolet region, efficient fluorescence emission in the visible light region, and the fluorescence quantum yield was as high as 0.91, which was in good agreement with the theoretical calculated value. In addition, the evaluation results of thermal stability, light stability and whitening performance on polyamide 66 fabric showed that the compound had excellent heat resistance, light resistance and whitening effect, and had good application potential in the field of fluorescent whitening of textiles.
Claims
1. A naphthyl-containing fluorescent whitening agent, characterized in that: The fluorescent whitening agent general structure is as follows: .
2. A naphthyl-containing fluorescent whitening agent as claimed in claim 1, characterized in that: The preparation process is as follows: Step 1: Preparation of 2,5-dibromo-4-boronic acid pinacol ester thiophene; 1.5726 g (6.50 mmol) 2,5-dibromothiophene, 1.6658 g (13.00 mmol) pinacol, 0.1849 g (0.16 mmol) tetrakis(triphenylphosphine)palladium were dissolved in 50 mL toluene and heated under reflux for 12 h; the solvent was evaporated under reduced pressure, and the residue was separated by silica gel column chromatography using petroleum ether / ethyl acetate (20:1) as the eluent to obtain 1.69 g of a white solid with a yield of 80.4%; Step 2: Preparation of 2,5-dibromo-3-naphthylthiophene; 1.6201 g (5.00 mmol) of 2,5-dibromo-4-boronic acid pinacol ester thiophene, 1.2456 g (5.00 mmol) of 3-bromomethylnaphthalene, 2.0732 g (15.00 mmol) of anhydrous potassium carbonate, 0.2311 g (0.20 mmol) of tetrakis(triphenylphosphine)palladium were added to a 50 mL round-bottom flask, N2 was replaced three times, 20 mL of degassed 1,4-dioxane and 10 mL of deionized water were injected, and the reaction was stirred at 90 °C for 10 h; after the reaction was completed, the reaction solution was poured into 50 mL of water, extracted with dichloromethane (30 mL × 3), the organic phases were combined and dried over anhydrous sodium sulfate; filtered, the solvent was removed by distillation under reduced pressure, and the crude product was separated by silica gel column chromatography [eluent: V (petroleum ether): V (ethyl acetate) = 30 : 1], 1.45 g of light yellow solid was obtained, with a yield of 72.3%; Step 3: Bromination reaction of 2,5-dibromo-3-naphthylthiophene; weigh 1.6051 g (4.00 mmol) 2,5-dibromo-3-naphthylthiophene and 0.7120 g (4.00 mmol) NBS in a 50 mL round-bottom flask, add 25 mL carbon tetrachloride, heat under reflux for 4 h in the dark; cool to room temperature, filter, wash the filter cake with a small amount of carbon tetrachloride, and dry to obtain 1.51 g of white solid powder, with a yield of 78.6%; Step 4: Preparation of 2-bromobenzothiazole-4-boronic acid pinacol ester; 2.1207 g (10.00 mmol) 2-bromobenzothiazole, 2.5626 g (20.00 mmol) pinacol, 3.4553 g (25.00 mmol) anhydrous potassium carbonate, 0.5778 g (0.50 mmol) tetrakis(triphenylphosphine)palladium were added to a 100 mL three-necked flask, N2 was replaced three times, 50 mL of degassed 1,4-dioxane was injected, and the reaction was stirred at 90 ° C for 12 h; the reaction solution was cooled to room temperature, filtered, the filter cake was washed with ethyl acetate, the filtrate was combined, and the solvent was evaporated under reduced pressure to obtain a crude product; the crude product was separated and purified by silica gel column chromatography [eluent: V (petroleum ether): V (ethyl acetate) = 5: 1] to obtain 2.13 g of a white solid with a yield of 84.8%; Step 5: Suzuki-Miyaura coupling reaction; 1.4406 g (3.00 mmol) 2,5-dibromo-4-bromomethyl-3-naphthylthiophene, 2.2602 g (9.00 mmol) 2-benzothiazole-4-boronic acid pinacol ester, 2.4873 g (18.00 mmol) anhydrous potassium carbonate, 0.3467 g (0.30 mmol) tetrakis(triphenylphosphine)palladium were added to a 100 mL three-necked flask, N2 was replaced three times, 60 mL of degassed 1,4-dioxane and 30 mL of deionized water were injected, and the reaction was stirred at 90 °C for 12 h; after the reaction was completed, the reaction solution was poured into 150 mL of water and extracted with ethyl acetate (50 mL × 3); the organic phases were combined, dried over anhydrous magnesium sulfate, filtered, desolventized, and the residue was subjected to silica gel column chromatography [eluent: V (petroleum ether): V (dichloromethane) = 1: 1] to separate 1.34 g of a yellow solid with a yield of 84.0%.